A Bibliometric Review of Agile Methodologies in Information Systems Development - Judijanto, Loso; Triwiyatno, Aris; Winardi, Bambang (Westscience Press, 2025)
This study presents a comprehensive bibliometric review of scholarly literature on agile methodologies within the context of information systems (IS) development, covering publications from 2000 to 2025. Using the Scopus database as the primary source, a total of relevant articles, conference papers, and reviews were analyzed through performance analysis and science mapping techniques with VOSviewer. The findings reveal that information systems development, information management, and software engineering are the most central and frequently occurring themes, acting as conceptual anchors for the field. Co-occurrence analysis identifies three thematic clusters: (1) technological and infrastructure dimensions, focusing on computational tools, artificial intelligence, and decision support systems; (2) organizational and managerial aspects, encompassing knowledge management, risk management, and user participation; and (3) software engineering and design methodologies, including agile frameworks and cross-domain applications. Overlay visualization indicates a thematic shift from early technical foundations toward broader socio-technical and strategic considerations, while density mapping highlights emerging areas such as agile manufacturing systems and outsourcing. Co-authorship and country collaboration networks show strong global research connectivity, with the United States, United Kingdom, and China leading in output and collaboration influence. The study contributes to both theory and practice by providing a structured knowledge map that integrates technical, organizational, and strategic perspectives of agile IS development, offering guidance for future research and practical implementation. Limitations include reliance on a single database, keyword-based search constraints, and the quantitative nature of bibliometric methods.